Las TIC, una oportunidad de participación ciudadana en los gobiernos subnacionales - Franciskovic, Jubitza (2020)
The present research explores the use of Information and Communications Technologies in the citizen participation of Subnational Governments with high digitization. For the analysis of the data, grounded theory was used, semistructured interviews were conducted with representatives of subnational governments in Metropolitan Lima and representatives of public and private institutions. The results highlight that subnational governments, following state e-government standards, offer numerous modern services through their web portals but these are underutilized by citizens.